Multiple Organ Dysfunction Syndrome Secondary to Multiple Wasp Stings: A Case Report: Multiple Organ Dysfunction Syndrome and Wasp Stings - Akter, Farhana; Jannatus Sabiha; Mostofa Kamal; Tahmina Jesmin; Delwar Hossain; Syed Saimul Huque (Journal of Pediatric Nephrology, 2025)
Background and Aim: Wasp stings can cause life-threatening conditions if not promptly managed. Symptoms can vary from local reactions to severe multi-organ dysfunction, such as acute kidney injury (AKI), acute liver failure (ALF), rhabdomyolysis, pulmonary edema, respiratory failure, hematological and neurological involvement, and even death. Emergency interventions are often needed. The purpose of this report was to increase awareness among clinicians about possible complications of wasp stings in order to provide early detection and proper management. Case Presentation: A six-year-old girl had been suffering from multiple wasp stings. She was diagnosed with multiple organ dysfunction syndrome (MODS), including hemolysis, AKI, liver injury, and respiratory failure. She was managed with renal replacement therapy and was ultimately discharged with normal renal function. Conclusion: Children with multiple wasp stings should be referred earlier for the initiation of proper management to improve the outcomes.